The Motivations and Impact of Social Media Adoption on Millennial Saudi Entrepreneurs in Hospitality Sector - Alajmi, Sarah (2020)
The dynamic evolution of social media transformed different dimensions in individuals’ lives. Universally, it became a multi-purpose channel to seek information, communicate with others and create entrepreneurial businesses. In Saudi Arabia, entrepreneurship is thriving particularly following the initiation of the Saudi Vision 2030, which aspires to diversify the economy. In light with the strong reforms, new sectors such as hospitality evolved, which witnessed increased number of SMEs by young entrepreneurs. The opportunistic value of social media becomes imperative for businesses to employ. Based on research, there was seen no prior studies concerning social media and entrepreneurship in hospitality. Therefore, this paper intends to study why millennial Saudi entrepreneurs in the hospitality sector are motivated to adopt social media for entrepreneurship, and how this adoption affects their SMEs. Qualitative Research method was employed through online interviews with 7 millennial Saudi entrepreneurs in the hospitality sector. Results showed that motivations are relate to the cost-efficiency of social media which allowed participants to use them as marketing approaches and facilitate the process of customer reach. Additionally, the effects of social media adoption on their SMEs were related to enhanced customer engagement, increased sales, developed creativity levels, expanded social capital and strengthened brand awareness. However, challenges were associated with customer satisfaction and reputation management, lack of essential resources, assessing social media effectiveness, changing market trends, trust issues and crisis management. This paper acts as initial exploration study; thus, results should not be generalised, and the data gathered is limited to the scope of the study.